The Development of Islamic Family Law in Indonesia - Siregar, Erni Sulhati Roudho (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
This article aims to delve deeply into the development of Islamic law in Indonesia, especially in the context of its interaction with customary law and positive law. This study uses a qualitative method with a historical approach to trace the dynamics of the development of the law from time to time. The data used in this study includes primary data, such as legal documents and historical archives, as well as secondary data consisting of literature reviews and previous research. The main focus of this research is to understand the development process of customary law, especially when customary law and Islamic law interact, complement each other, and achieve harmony without causing significant controversy. In addition, this study also highlights how the judicial process runs when the government implements a policy of legal uniformity through codification and unification of laws. This includes the incorporation of customary law values and Islamic law into a positive legal framework regulated in laws and regulations. This research is expected to provide an overview of how customary law still survives today as an integral part of the life of Indonesian people. Despite the challenges of modernization, customary law is still recognized for its existence and plays an important role in shaping the legal identity of the community, as well as coexisting with Islamic law and positive law in creating social harmony and legal justice.